Study on the fusion of sports and medicine in China from 2012 to 2021: A bibliometric analysis via CiteSpace - Si-Jing Tu; Si-Jing Tu; Chen Jin; Bu-Tong Chen; An-Ying Xu; Chao Luo; Xiao-He Wang (Frontiers Media S.A., 2022)
ObjectiveTo analyze the research hot spots and frontiers of studies on of the fusion of sports and medicine (FSM) in China in recent decade via CiteSpace.MethodsRelevant publications related FSM published from January 1, 2012 to December 31, 2021 were obtained from the China National Knowledge Infrastructure (CNKI) database. CiteSpace software was used to analyze the amount of publications, institutions and keywords using standard bibliometric indicators.ResultsA total of 729 publications on FSM were identified, and 688 qualified records were included in the final analysis. Between 2012 to 2021, the number of publications showed a trend of growth, albeit with certain fluctuations. The authors of these publications were mainly from universities or colleges with sports background. The institution leading the study was the Beijing Sport University (n = 20), the most prolific (n =12) and most-cited (224 times) author was Guo JJ from Capital University of Physical Education Sports. The journal with most publications on FSM was Contemporary Sports Technology (n =74). The analysis of keywords showed that the "FSM" had the highest frequency (n = 269), "integration of sports and medicine" had the strongest citation bursts (4.82), "national fitness" had the highest centrality (0.97) in recent decade, and 15 clusters of keywords were produced by log-likelihood ratio (all silhouette value >0.9).ConclusionThe findings of this bibliometric study analyse the current status and trends in the FSM in China, which may help to identify hot topics, explore new study directions for scholars and policymakers in the future.